ANALISIS KINERJA SUPPLIER BBM PADA PERUSAHAAN JASA PERKAPALAN DENGAN ANALYTICAL HIERARCHY PROCESS - Putu Wira Pradnya Santoso; yugowati praharsi (Proceeding Maritime Business Management Conference, 2024)
Supplier performance assessment in shipping service companies so far only includes price criteria and administrative completeness. This performance assessment is not optimal, so the problem of negligence caused by some suppliers continues to occur every year. More than 50% of suppliers have committed negligence at least once. Based on these problems, this research was conducted to determine the criteria and sub-criteria that affect supplier performance assessment. Furthermore, assessing supplier performance based on predetermined criteria and subcriteria. The AHP method is used for weighting criteria and sub-criteria for performance assessment. The results obtained with the AHP method are the quality criteria getting the largest weight, namely (0.326), Price (0.300), Responsiveness (0.136), Delivery (0.108), Flexibility (0.065), Administration (0.039), Engineering (0.026). The results of weighting the subcriteria get the results of the sub-criteria with the highest weight are the price offered (0.210), quality of BBM products (0.179), work according to SOP (0.101), accuracy of the number of deliveries (0.091), accuracy of the amount of delivery (0.091), and providing discounts (0.090).